Isostructural and Multivalent Anion Substitution toward Improved Phosphate Cathode Materials for Sodium‐Ion Batteries. Issue 16 (5th March 2020) - Wang, Mei‐Yi; Guo, Jin‐Zhi; Wang, Zhi‐Wei; Gu, Zhen‐Yi; Nie, Xue‐Jiao; Yang, Xu; Wu, Xing‐Long
Abstract: Polyanion‐type phosphate materials are highly promising cathode candidates for next‐generation batteries due to their excellent structural stability during cycling; however, their poor conductivity has impeded their development. Isostructural and multivalent anion substitution combined with carbon coating is proposed to greatly improve the electrochemical properties of phosphate cathode in sodium‐ion batteries (SIBs). Specifically, multivalent tetrahedral SiO4 4− substitute for PO4 3− in Na3 V2 (PO4 )3 (NVP) lattice, preparing the optimal Na3.1 V2 (PO4 )2.9 (SiO4 )0.1 with high‐rate capability (delivering a high capacity of 82.5 mAh g −1 even at 20 C) and outstanding cyclic stability ( ≈ 98% capacity retention after 500 cycles at 1 C). Theoretical calculation and experimental analyses reveal that the anion‐substituted Na3.1 V2 (PO4 )2.9 (SiO4 )0.1 reduces the bandgap of NVP lattice and enhanced its structural stability, Na + ‐diffusion kinetics and electronic conductivity. This strategy of multivalent and isostructural anion substitution chemistry provides a new insight to develop advanced phosphate cathodes. Abstract : Na3+ x V2 (PO4 )3− x (SiO4 ) x (0 ≤ x ≤ 0.15) cathode materials are prepared via substitution of the inactive PO4 3− sites in Na3 V2 (PO4 )3 with isostructural SiO4 4− anions. The substitution effects on crystal structure, electrochemical properties, Na + ‐diffusion kinetics and electronic conductivity are systematically investigated. Multivalent and isostructural anionic substitution provides a new strategy for designing polyanionic materials of sodium‐ion batteries.